Chemical Properties of Modified Mahogany Wood by Heat Treatment - Ganis Lukmandaru; Dewi Susanti; Ragil Widyorini (Foresty Faculty of Hasanuddin University, 2018)
Mahogany woods from community forests generally have relatively low qualities due to lack of maintenance activities and for their young harvesting stage. Heat treatment is known as wood modification method that could improve the quality of the wood. The aim of this study was to determine the interaction effect of temperature and method of heat treatment on the chemical properties of young mahogany wood. Materials used in this research were mahogany wood boards from community forest which were heat-treated using oven and steam methods performed at the temperature of 90°C, 120°C, and 150oC for 2 hours. In this research, some chemical changes were analyzed. Results of the research showed that the interaction of temperature and heat treatment method gave a significant decreasing on the pentosan amount, and hot-water extractive solubility, particularly the steaming at 150oC. The increasing temperature of heat treatment significantly decreased the content of holocellulose, α-cellulose, hemicellulose, and pH values whereas it increased lignin content, extractives (cold-water and alcohol-benzene extractives) and solubility in 1% NaOH. Steaming method provided lower levels in the content of holocellulose, ethanol-benzene extract, cold-water solubility, and pH values compared to the oven heating. However, the steaming method over 1200C should be considered as it would reduce the wood strengths.